The impact of social-relationship patterns on worsening mental health among the elderly during the COVID-19 pandemic: Evidence from Hungary - Ágnes Győri (Elsevier, 2023)
Evidence indicates the coronavirus pandemic has severely affected the oldest age group: in Hungary 92.7 per cent of those who died due to COVID-19 infection were 60 years of age or older. The age structure of the deceased was very similar in other countries. As, due to their underlying health status, elderly people are more vulnerable to the serious diseases caused by the coronavirus, strict government restrictions were introduced worldwide to protect them when the epidemic broke out. However, this social isolation can cause severe psychological and emotional strain. The study aim was to examine how patterns of social relationships were related to changes in mental health of the elderly during the COVID-19 pandemic in Hungary. We used the database of SHARE COVID-19 for our analysis. Descriptive and multivariate analyses were conducted. Findings of this study suggest that the network lacking contacts increases the severity of depression, anxiety, sleeping disorders, and loneliness the most among the elderly. Interestingly, the group with an intense close-knit network had a higher risk of worsening mental symptoms compared to multiple contact actives. Moreover, electronic communication - telephone, Skype - did not help either: there was a particularly high probability of worsening depression in this group. Another interesting result is that both in the group dominated by family contacts and among those with multiple relationships, the chances of worsening mental symptoms were lower, thus, personal contact - whether they include family members or other acquaintances - is truly protective. Results demonstrate that both the network characterised by lack of contact network and electronic contact activity contribute to greater risk of worsening mental health within elderly. A network pattern characterised by various types and forms of contacts is the most beneficial to mental health, and intensive contacts of limited scope alone are not sufficient to protect mental health.